Literary Competence For The Teaching Of Literature In Second Language Educational Context - Hapsari, Astri (English Education Department, Universitas Islam Indonesia, 2011)
This essay analyzes the use of literary works in second language educational context. It highlights the importance of literary competence and the implications at stake for the teaching of literature such as: the importance of setting the purpose in teaching literature, the need of considering literature teaching as product versus literature teaching as process and the necessitate of relating literature, language and culture. A brief analysis of the author's experience in using the literary texts in teaching English as a foreign language is also presented. From the discussions of the related literature, further research is recommended to settle the arguments of poetic versus hermeneutic approach in teaching literature as object of study. Moreover, appropriate balance for language, literature and culture for teaching literature as a topic or resources is suggested.